The roles of manufacturers in achieving effective ISO 14001 certification - 463164 Siah, Bee Yong (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Kejuruteraan (Awam - Pengurusan Alam Sekitar)) - Universiti Teknologi Malaysia, 2005